Alegoria szczęśliwego panowania pędzla Jana Reisnera z łazienki ogrodu włoskiego zamku w Żółkwii - Kossowski, Maciej Dariusz (Studia Europaea Gnesnensia, 2024)
Jan Reisner’s painting from the castle in Żółkiew has been referred to on several occasions in art history literature, but the personifications depicted there were erroneously identified. In this paper, the author challenges the assertions made earlier. An iconographic analysis combines all elements of the composition into a coherent whole, thus revealing novel, hitherto unknown symbolism of the representation. The painting allegorically anticipated the state of affairs in the country after king Jan III’s return from the autumn campaign of 1684, while the choice of theme demonstrates the painter’s in-depth knowledge of antiquity, which he drew on when creating the work. Also, the allegorical import of the piece dictated where the painting would be exhibited, as the location was anything but insignificant. The painting was placed in the bath of the Italian garden of the king’s residence in Żółkiew, and hung in the middle room above the bed, as stated in the inventory of 1726, a fact established and reported for the first time in this study. These new findings have raised the cultural and artistic value of the work.